Pathogenesis and therapeutic targeting of aberrant MYC expression in haematological cancers. (24th November 2017) - Schick, Markus; Habringer, Stefan; Nilsson, Jonas A.; Keller, Ulrich
Summary: Identifying and therapeutically targeting cancer cell liabilities is of utmost importance in order to improve the treatment of patients with malignancies of poor prognosis. The MYC family genes ( MYC, MYCN and MYCL ) are among the most deregulated proto‐oncogenes in human cancer. Aberrant MYC expression is frequently associated with poor prognosis. Although many aspects of MYC‐mediated tumour biology are well characterized, there are currently no effective means for targeting MYC in a specific manner that have been established for clinical use. This review first discusses the role of MYC in the pathogenesis of haematopoietic malignancies, and secondly summarizes how insight into MYC functions could be translated into therapeutic approaches. In particular, we will address the possibilities of taking advantage of MYC‐induced cancer cell vulnerabilities that could be exploited in terms of synthetic lethal interactions.